Analysis Cracking Corrosion on Carbon Steel Pipes API 5L-X65 In Solution 7700 ml Aquades, 250 ml Acetic Acid and 50 ml Ammonia with Gas CO2 and H2S in Saturation Condition - Nendi Suhendi Syafei; Darmawan Hidayat; Emilliano Emilliano; Liu Kin Men (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
The oil and gas industry exploration that will generally be followed by corrosive substances including sweet gas (eg H2S and CO2), it will result in corrosion event. The corrosion stress cracking will cause the carbon steel pipe to break so that production oil and gas can be stopped. The research aims in this paper is to analyze the corrosion event of carbon steel pipe in laboratory scale on acid environment with the existence of sweet gas H2O and CO2 by using three points loading method. This research uses carbon steel pipe API 5L-X65 which stay in condensation environment of 7700 ml aquades, 250 ml acetic acid and 50 ml ammonia, then filled sweet gas CO2 and H2S in saturated state. Based on the test results of microstructure and microscope polarized, there is a phenomenon corrosion stress cracking, i.e transgranular stress cracking corrosion and intergranular stress cracking corrosion. The accelerate corrosion that happened at the test sample will be greater if ever greater given deflection for the time of the same presentation. Crack deepness in the test of the test sample will deeper if ever greater given deflection. The cracks in the sample test will deeper if it was given stress σ greater for the same exposure time.